Ultrathin polymer solid electrolyte membrane, preparation method and battery thereof

By using nano-scale cellulose and casting preparation technology in polymer solid electrolyte membranes, the problem of poor mechanical properties of polymer electrolyte membranes is solved, ultra-thin thickness control and energy density improvement are achieved, production costs are reduced, and production costs are good commercial application prospects.

CN119253048APending Publication Date: 2025-01-03XI AN JIAOTONG UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411387113.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Due to poor mechanical properties, the existing polymer solid electrolyte membranes have thicker thickness, which reduces electrical conductivity and energy density, and has a higher production cost.

Method used

Using nano-scale cellulose as the matrix material, combined with casting method to prepare ultra-thin polymer solid electrolyte membranes. By adjusting the ratio of nano-scale cellulose, polymer polymer and electrolyte salts, the ultra-thin thickness control of the electrolyte membrane is achieved and the machinery is improved. Intensity and energy density.

Benefits of technology

The ultra-thin thickness of the electrolyte membrane (10μm and below) is controlled, the mechanical strength and cycle life are improved, the manufacturing cost is reduced, and it is compatible with large-scale production, and has good commercial application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119253048A_ABST
    Figure CN119253048A_ABST
Patent Text Reader

Abstract

The invention discloses an ultrathin polymer solid electrolyte membrane, a preparation method and a battery thereof. The electrolyte membrane is prepared from the following raw materials: nanoscale cellulose, a high-molecular polymer, a solvent and electrolyte salt, the mass ratio of the nanoscale cellulose to the high-molecular polymer to the solvent to the electrolyte salt is (1-3): 20: (20-30): (6-16). According to the invention, the nanoscale cellulose is added into the high-molecular polymer and the electrolyte salt, and the nanoscale cellulose has good biodegradability, is non-toxic and harmless, and has no pollution to the environment. Moreover, the added nanoscale cellulose has the cellulose purity of 95%, excellent mechanical strength and high elastic modulus and tensile strength, and compared with the prior art, the mechanical strength of the polymer electrolyte membrane is greatly improved, so that the preparation of an ultrathin solid electrolyte becomes possible.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrochemical energy storage polymer solid electrolyte membrane preparation, and in particular to an ultra-thin polymer solid electrolyte membrane, a preparation method and a battery thereof. Background Art

[0002] For decades, lithium-ion batteries have dominated the energy storage market due to their high energy density and long cycle life, but they are prone to combustion and explosion due to the presence of liquid electrolytes and lithium dendrites. Solid electrolytes have been widely studied due to their excellent safety and superior ability to inhibit the growth of lithium dendrites.

[0003] Inorganic solid electrolytes impose high interfacial resistance at the solid-solid electrode-electrolyte interface, while polymer electrolytes have received more attention due to their superior flexibility and good interfacial compatibility. However, the currently popular polymer solid separators have poor mechanical properties, resulting in thick thickness, which greatly reduces the conductivity of the electrolyte separator and the energy density of solid-state batteries.

[0004] Li, Y et al. improved the mechanical strength of polyethylene oxide electrolyte by adding 3% bacterial cellulose (BC) to polyethylene oxide (Li, Y. et al. Bacterial Cellulose Composite Solid Polymer Electrolyte With High Tensile Strength and Lithium Dendrite Inhibition for Long Life Battery. Energy & Environmental Materials 4, 434-443, doi: 10.1002 / eem2.12122 (2020)), but the content of BC added was low and its mechanical properties were not very good. Therefore, the thickness of the polymer electrolyte membrane was relatively thick (73μm), which made the conductivity of the polymer lower and the energy density of the battery lower.

[0005] Polyethylene oxide has good lithium salt solubility and high ionic conductivity at 60°C, but has the disadvantage of poor mechanical properties. In order to improve the mechanical strength of polyethylene oxide, polyethylene oxide is generally poured into the matrix material, but this will increase the thickness of the electrolyte, reduce the energy density, and increase the production cost to a certain extent. Summary of the invention

[0006] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide an ultra-thin polymer solid electrolyte membrane, a preparation method and a battery thereof, using nano-cellulose as a matrix material and combining the casting method to prepare the ultra-thin polymer solid electrolyte membrane, thereby realizing the preparation of an ultra-thin solid electrolyte membrane with controllable thickness, improving the energy density and reducing the manufacturing cost; at the same time, the present invention also provides a battery containing the ultra-thin polymer solid electrolyte membrane.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0008] An ultra-thin polymer solid electrolyte membrane, the raw materials of which include nano-cellulose, high molecular polymer, solvent and electrolyte salt; in terms of mass ratio, nano-cellulose: high molecular polymer: solvent: electrolyte salt = (1-3): 20: (20-30): (6-16).

[0009] The nano-scale cellulose is one of nano-cellulose and bacterial cellulose.

[0010] The nano-scale cellulose has a cellulose purity of 90%-95%, a high Young's modulus of 15-35 GPa, and a tensile strength of 200-300 MPa.

[0011] The solvent is one of water, acetonitrile, N-methylpyrrolidone and N,N-dimethylformamide.

[0012] The high molecular polymer is one of polyethylene oxide, polyvinylidene fluoride and polyacrylonitrile.

[0013] The electrolyte salt is one of LiTFSI, LiClO4, LiFSI, NaTFSI, and NaClO4.

[0014] A method for preparing an ultrathin polymer solid electrolyte membrane comprises the following steps:

[0015] Step 1, weighing nano-cellulose, high molecular polymer, solvent and electrolyte salt according to the mass ratio = (1-3): 20: (20-30): (6-16);

[0016] Dispersing nano-cellulose in a solvent to obtain a nano-cellulose dispersion; in terms of mass ratio, nano-cellulose: solvent = (1-3): (20-30);

[0017] Step 2, adding a high molecular weight polymer and an electrolyte salt to the nanometer-sized cellulose dispersion prepared in step 1 and mixing them evenly to obtain a polymer solid electrolyte precursor solution, wherein, by mass ratio, nanometer-sized cellulose: high molecular weight polymer: electrolyte salt = (1-3): 20: (6-16);

[0018] Step 3, coating the polymer solid electrolyte precursor solution prepared in step 2 on a strippable carrier, using a scraper for scraping, with the scraper height set to 100-750 μm;

[0019] Step 4, drying the electrolyte membrane obtained in step 3 until there is no water film on the surface, the drying temperature is 60-100° C., and the drying time is 10 min-20 min, to obtain the electrolyte membrane;

[0020] Step 5, peel off the electrolyte membrane obtained in step 4 and vacuum dry it, the vacuum degree is 0-0.098MPa, the drying temperature is set to 80-100°C, and the drying time is set to 24-48h to obtain an ultra-thin polymer solid electrolyte membrane.

[0021] A solid-state polyethylene oxide-based battery comprises the above-mentioned ultra-thin polymer solid electrolyte membrane.

[0022] Compared with the prior art, the beneficial effects of the present invention are:

[0023] 1. The present invention adds nano-cellulose to the high molecular polymer and electrolyte salt. The nano-cellulose has good biodegradability, is non-toxic and harmless, and does not pollute the environment. In addition, the added nano-cellulose has a cellulose purity of up to 95%, excellent mechanical strength, high elastic modulus and tensile strength. Compared with the prior art, the mechanical strength of the polymer electrolyte membrane is greatly improved, making it possible to prepare an ultra-thin solid electrolyte.

[0024] 2. The present invention adopts the casting method to prepare the electrolyte membrane, which can achieve ultra-thin thickness (10μm and below) of the electrolyte membrane and controllable thickness, and is compatible with the current roll-to-roll production process and can realize large-scale production. Compared with the existing technology, the present invention has the characteristics of good compatibility and strong flexibility.

[0025] 3. The electrolyte membrane prepared by the present invention reduces the impedance of the electrolyte compared to the traditional polyethylene oxide electrolyte membrane and achieves a long cycle life at 60 degrees.

[0026] In summary, the present invention can obtain an ultra-thin solid electrolyte with a thickness of less than 10 μm and controllable thickness, and is simple and fast, not limited by the preparation environment, and is an effective and economical method for preparing solid electrolyte membranes. The prepared polymer solid electrolyte membrane can take into account both ultra-thin thickness and excellent mechanical strength, and has broad prospects for large-scale production and commercial application. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is the appearance picture of the BC polyethylene oxide lithium salt electrolyte membrane prepared in Example 6 of the present invention.

[0028] Figure 2 This is a thickness control diagram of the BC polyethylene oxide lithium salt electrolyte membrane prepared in Example 6 of the present invention.

[0029] Figure 3 This is a comparison chart of lithium symmetric cycle data of the BC polyethylene oxide lithium salt electrolyte membrane prepared in Example 6 of the present invention and a common polyethylene oxide membrane. DETAILED DESCRIPTION

[0030] The present invention will be described in detail below in conjunction with the accompanying drawings.

[0031] Example 1

[0032] An ultra-thin polymer solid electrolyte membrane, the raw materials of which include bacterial cellulose, polyethylene oxide, water and LiTFSI; calculated by mass ratio, bacterial cellulose: polyethylene oxide: water: LiTFSI=1:20:20:6.

[0033] A method for preparing an ultrathin polymer solid electrolyte membrane comprises the following steps:

[0034] Step 1, dispersing bacterial cellulose in water to obtain a bacterial cellulose dispersion; the mass ratio of bacterial cellulose to water is 1:20; the bacterial cellulose has a cellulose purity of 90%, a high Young's modulus of 25 GPa, and a tensile strength of 200 MPa;

[0035] Step 2, adding polyethylene oxide and LiTFSI to the bacterial cellulose dispersion prepared in step 1 and mixing them evenly to obtain a polymer solid electrolyte precursor solution, wherein the mass ratio of bacterial cellulose: polyethylene oxide: LiTFSI is 1:20:6;

[0036] Step 3, coating the polymer solid electrolyte precursor solution prepared in step 2 on a strippable carrier, using a scraper for scraping, with the scraper height set to 100 μm;

[0037] Step 4, placing the electrolyte membrane obtained in step 3 in a forced air oven, setting the oven temperature to 60° C. and drying for 10 min;

[0038] Step 5, peel off the electrolyte membrane obtained in step 4, put it into a vacuum oven with a vacuum degree of 0.02 MPa, a drying temperature set to 80°C, and a drying time set to 24 hours to obtain an ultra-thin polymer solid electrolyte membrane.

[0039] Example 2

[0040] An ultra-thin polymer solid electrolyte membrane, the raw materials of which include bacterial cellulose, polyethylene oxide, water and LiClO4; calculated by mass ratio, bacterial cellulose: polyethylene oxide: water: LiClO4=1.5:20:22:8.

[0041] A method for preparing an ultrathin polymer solid electrolyte membrane comprises the following steps:

[0042] Step 1, dispersing bacterial cellulose in water to obtain a bacterial cellulose dispersion; the mass ratio of bacterial cellulose to water is 1.5:22; the bacterial cellulose has a cellulose purity of 91%, a high Young's modulus of 15 GPa, and a tensile strength of 220 MPa;

[0043] Step 2, adding polyethylene oxide and LiClO4 to the bacterial cellulose dispersion prepared in step 1 and mixing them evenly to obtain a polymer solid electrolyte precursor solution, wherein the mass ratio of bacterial cellulose: polyethylene oxide: LiClO4 is 1.5:20:8;

[0044] Step 3, coating the polymer solid electrolyte precursor solution prepared in step 2 on a strippable carrier, using a scraper for scraping, with the scraper height set to 200 μm;

[0045] Step 4, placing the electrolyte membrane obtained in step 3 in a forced air oven, setting the oven temperature to 65°C and drying time to 12 minutes;

[0046] Step 5, peel off the electrolyte membrane obtained in step 4, put it into a vacuum oven with a vacuum degree of 0.04 MPa, a drying temperature of 85°C and a drying time of 30 hours to obtain an ultra-thin polymer solid electrolyte membrane.

[0047] Example 3

[0048] An ultra-thin polymer solid electrolyte membrane, wherein raw materials of the electrolyte membrane include bacterial cellulose, polyethylene oxide, water and LiFSI; in terms of mass ratio, bacterial cellulose: polyethylene oxide: water: LiFSI=1.5:20:24:9.

[0049] The electrolyte membrane had a thickness of 10 μm and a uniform thickness.

[0050] The electrolyte membrane has a uniform surface morphology.

[0051] A method for preparing an ultrathin polymer solid electrolyte membrane comprises the following steps:

[0052] Step 1, dispersing bacterial cellulose in water to obtain a bacterial cellulose dispersion; the mass ratio of bacterial cellulose to water is 1.5:24; the bacterial cellulose has a cellulose purity of 92%, a high Young's modulus of 18 GPa, and a tensile strength of 240 MPa;

[0053] Step 2, adding polyethylene oxide and LiFSI to the bacterial cellulose dispersion prepared in step 1 and mixing them evenly to obtain a polymer solid electrolyte precursor solution, wherein the mass ratio of bacterial cellulose: polyethylene oxide: LiFSI is 1.5:20:9;

[0054] Step 3, coating the polymer solid electrolyte precursor solution prepared in step 2 on a strippable carrier, using a scraper for scraping, with the scraper height set to 400 μm;

[0055] Step 4, placing the electrolyte membrane obtained in step 3 in a forced air oven, setting the oven temperature to 70°C and drying time to 15 minutes;

[0056] Step 5, peel off the electrolyte membrane obtained in step 4, put it into a vacuum oven, set the vacuum degree to 0.05MPa, set the drying temperature to 90°C, and set the drying time to 32h to obtain an ultra-thin polymer solid electrolyte membrane.

[0057] Example 4

[0058] An ultra-thin polymer solid electrolyte membrane, the raw materials of which include bacterial cellulose, polyacrylonitrile, water and LiTFSI; calculated by mass ratio, bacterial cellulose: polyacrylonitrile: water: LiTFSI = 2:20:25:10.

[0059] The electrolyte membrane had a thickness of 10 μm and a uniform thickness.

[0060] The electrolyte membrane has a uniform surface morphology.

[0061] A method for preparing an ultrathin polymer solid electrolyte membrane comprises the following steps:

[0062] Step 1, dispersing bacterial cellulose in water to obtain a bacterial cellulose dispersion; the mass ratio of bacterial cellulose to water is 2:25; the bacterial cellulose has a cellulose purity of 93%, a high Young's modulus of 22 GPa, and a tensile strength of 260 MPa;

[0063] Step 2, adding polyacrylonitrile and LiTFSI to the bacterial cellulose dispersion prepared in step 1 and mixing them evenly to obtain a polymer solid electrolyte precursor solution, wherein the mass ratio of bacterial cellulose: polyacrylonitrile: LiTFSI is 2:20:10;

[0064] Step 3, coating the polymer solid electrolyte precursor solution prepared in step 2 on a strippable carrier, using a scraper for scraping, with the scraper height set to 500 μm;

[0065] Step 4, placing the electrolyte membrane obtained in step 3 in a forced air oven, setting the oven temperature to 75°C and drying time to 17 minutes;

[0066] Step 5, peel off the electrolyte membrane obtained in step 4, put it into a vacuum oven with a vacuum degree of 0.06 MPa, a drying temperature of 95°C and a drying time of 36 hours to obtain an ultra-thin polymer solid electrolyte membrane.

[0067] Example 5

[0068] An ultra-thin polymer solid electrolyte membrane, wherein raw materials of the electrolyte membrane include bacterial cellulose, polyacrylonitrile, water and LiFSI; in terms of mass ratio, bacterial cellulose: polyacrylonitrile: water: LiFSI = 2.5:20:27:12.

[0069] The electrolyte membrane had a thickness of 14 μm and a uniform thickness.

[0070] The electrolyte membrane has a uniform surface morphology.

[0071] A method for preparing an ultrathin polymer solid electrolyte membrane comprises the following steps:

[0072] Step 1, dispersing bacterial cellulose in water to obtain a bacterial cellulose dispersion; the mass ratio of bacterial cellulose to water is 2.5:27; the bacterial cellulose has a cellulose purity of 94%, a high Young's modulus of 24 GPa, and a tensile strength of 280 MPa;

[0073] Step 2, adding polyacrylonitrile and LiFSI to the bacterial cellulose dispersion prepared in step 1 and mixing evenly to obtain a polymer solid electrolyte precursor solution, wherein the mass ratio of bacterial cellulose: polyacrylonitrile: LiFSI is 2.5:20:12. ;

[0074] Step 3: coating the polymer solid electrolyte precursor solution prepared in step 2 on a strippable carrier by scraping with a scraper, wherein the scraper height is set to 750 μm.

[0075] Step 4, placing the electrolyte membrane obtained in step 3 in a forced air oven, setting the oven temperature to 80°C and drying for 20 minutes;

[0076] Step 5, peel off the electrolyte membrane obtained in step 4, put it into a vacuum oven with a vacuum degree of 0.07 MPa, a drying temperature of 80°C and a drying time of 48 hours to obtain an ultra-thin polymer solid electrolyte membrane.

[0077] Example 6

[0078] An ultra-thin polymer solid electrolyte membrane, the raw materials of which include bacterial cellulose, polyvinylidene fluoride, water and LiTFSI; calculated by mass ratio, bacterial cellulose: polyvinylidene fluoride: water: LiTFSI = 3:20:30:16.

[0079] The electrolyte membrane had a thickness of 10 μm and a uniform thickness.

[0080] The electrolyte membrane has a uniform surface morphology.

[0081] A method for preparing an ultrathin polymer solid electrolyte membrane comprises the following steps:

[0082] Step 1, dispersing bacterial cellulose in water to obtain a bacterial cellulose dispersion; the mass ratio of bacterial cellulose to water is 3:30; the bacterial cellulose has a cellulose purity of 95%, a high Young's modulus of 26 GPa, and a tensile strength of 300 MPa;

[0083] Step 2, adding polyvinylidene fluoride and LiTFSI to the bacterial cellulose dispersion prepared in step 1 and mixing them evenly to obtain a polymer solid electrolyte precursor solution, wherein the mass ratio of bacterial cellulose: polyvinylidene fluoride: LiTFSI is 3:20:16;

[0084] Step 3, coating the polymer solid electrolyte precursor solution prepared in step 2 on a strippable carrier, using a scraper for scraping, with the scraper height set to 200 μm;

[0085] Step 4, placing the electrolyte membrane obtained in step 3 in a forced air oven, setting the oven temperature to 60° C. and drying time to 15 min;

[0086] Step 5, peel off the electrolyte membrane obtained in step 4, put it into a vacuum oven with a vacuum degree of 0.09 MPa, a drying temperature set to 80°C, and a drying time set to 24 hours to obtain an ultra-thin polymer solid electrolyte membrane.

[0087] Example 7

[0088] An ultra-thin polymer solid electrolyte membrane, the raw materials of which include nanocellulose, polyvinylidene fluoride, N-methylpyrrolidone and LiTFSI; in terms of mass ratio, nanocellulose: polyvinylidene fluoride: N-methylpyrrolidone: LiTFSI=2:20:26:12.

[0089] The electrolyte membrane had a thickness of 10 μm and a uniform thickness.

[0090] The electrolyte membrane has a uniform surface morphology.

[0091] A method for preparing an ultrathin polymer solid electrolyte membrane comprises the following steps:

[0092] Step 1, dispersing nanocellulose in N-methylpyrrolidone to obtain a nanocellulose dispersion; in terms of mass ratio, nanocellulose: N-methylpyrrolidone = 2:26; the nanocellulose has a cellulose purity of 90%, a high Young's modulus of 28 GPa, and a tensile strength of 250 MPa;

[0093] Step 2, adding polyvinylidene fluoride and LiTFSI to the nanocellulose dispersion prepared in step 1 and mixing them evenly to obtain a polymer solid electrolyte precursor solution, wherein the mass ratio of nanocellulose: polyvinylidene fluoride: LiTFSI is 2:20:12;

[0094] Step 3, coating the polymer solid electrolyte precursor solution prepared in step 2 on a strippable carrier by scraping with a scraper, wherein the scraper height is set to 250 μm;

[0095] Step 4, placing the electrolyte membrane obtained in step 3 in a forced air oven, setting the oven temperature to 70°C and drying time to 20 minutes;

[0096] Step 5, peel off the electrolyte membrane obtained in step 4, put it into a vacuum oven, set the vacuum degree to 0.09 MPa, set the drying temperature to 80°C, and set the drying time to 30 hours to obtain an ultra-thin polymer solid electrolyte membrane.

[0097] Example 8

[0098] An ultra-thin polymer solid electrolyte membrane, wherein the raw materials of the electrolyte membrane include nanocellulose, polyacrylonitrile, acetonitrile and LiTFSI; in terms of mass ratio, nanocellulose: polyacrylonitrile: acetonitrile: LiTFSI = 1:20:22:10.

[0099] The electrolyte membrane had a thickness of 10 μm and a uniform thickness.

[0100] The electrolyte membrane has a uniform surface morphology.

[0101] A method for preparing an ultrathin polymer solid electrolyte membrane comprises the following steps:

[0102] Step 1, dispersing nanocellulose in acetonitrile to obtain a nanocellulose dispersion; the mass ratio of nanocellulose to acetonitrile is 1:22; the nanocellulose has a cellulose purity of 95%, a high Young's modulus of 30 GPa, and a tensile strength of 230 MPa;

[0103] Step 2, adding polyacrylonitrile and LiTFSI to the nanocellulose dispersion prepared in step 1 and mixing them evenly to obtain a polymer solid electrolyte precursor solution, wherein the mass ratio of nanocellulose: polyacrylonitrile: LiTFSI is 1:20:10;

[0104] Step 3, coating the polymer solid electrolyte precursor solution prepared in step 2 on a strippable carrier, using a scraper for scraping, with the scraper height set to 200 μm;

[0105] Step 4, placing the electrolyte membrane obtained in step 3 in a forced air oven, setting the oven temperature to 80°C and drying time to 15 minutes;

[0106] Step 5, peel off the electrolyte membrane obtained in step 4, put it into a vacuum oven with a vacuum degree of 0.098 MPa, a drying temperature set to 90°C, and a drying time set to 24 hours to obtain an ultra-thin polymer solid electrolyte membrane.

[0107] Example 9

[0108] An ultra-thin polymer solid electrolyte membrane, the raw materials of which include nanocellulose, polyvinylidene fluoride, N,N-dimethylformamide and LiTFSI; in terms of mass ratio, nanocellulose: polyvinylidene fluoride: N,N-dimethylformamide: LiTFSI=3:20:28:16.

[0109] The electrolyte membrane had a thickness of 10 μm and a uniform thickness.

[0110] The electrolyte membrane has a uniform surface morphology.

[0111] A method for preparing an ultrathin polymer solid electrolyte membrane comprises the following steps:

[0112] Step 1, dispersing nanocellulose in N,N-dimethylformamide to obtain a nanocellulose dispersion; the mass ratio of nanocellulose to N,N-dimethylformamide is 3:28; the nanocellulose has a cellulose purity of 92%, a high Young's modulus of 35 GPa, and a tensile strength of 270 MPa;

[0113] Step 2, adding polyvinylidene fluoride and LiTFSI to the nanocellulose dispersion prepared in step 1 and mixing them evenly to obtain a polymer solid electrolyte precursor solution, wherein the mass ratio of nanocellulose: polyvinylidene fluoride: LiTFSI is 3:20:16;

[0114] Step 3, coating the polymer solid electrolyte precursor solution prepared in step 2 on a strippable carrier, using a scraper for scraping, with the scraper height set to 300 μm;

[0115] Step 4, placing the electrolyte membrane obtained in step 3 in a forced air oven, setting the oven temperature to 80°C and drying for 20 minutes;

[0116] Step 5, peel off the electrolyte membrane obtained in step 4, put it into a vacuum oven, set the vacuum degree to 0.092MPa, set the drying temperature to 80°C, and set the drying time to 30h to obtain an ultra-thin polymer solid electrolyte membrane.

[0117] Figure 1 The present invention is a process of transferring the ultra-thin polyethylene oxide electrolyte membrane prepared in Example 1. It can be found that the ultra-thin polyethylene oxide electrolyte membrane has excellent mechanical properties. When stretched, the ultra-thin polyethylene oxide electrolyte membrane does not break. The thickness of the electrolyte membrane is 3μm-14μm, and it has the prospect of large-scale production.

[0118] Figure 2 The thickness of the ultra-thin polyethylene oxide electrolyte membrane prepared in Example 1 of the present invention is tested by using a thickness gauge. It can be clearly found that when the scraper height is 750 μm, the thickness of the ultra-thin polyethylene oxide electrolyte membrane can reach 22 μm; when the scraper height is reduced to 400 μm, the thickness of the ultra-thin polyethylene oxide electrolyte membrane can be reduced to 10 μm; when the scraper height is further reduced to 200 μm, the thickness of the ultra-thin polyethylene oxide electrolyte membrane is only 8 μm, achieving both ultra-thin thickness and excellent mechanical properties. It can be seen that BC plays an important role in improving the mechanical properties of the electrolyte.

[0119] Figure 3 In order to test the cycle performance of the lithium symmetric battery assembled with the ultra-thin polyethylene oxide electrolyte membrane of Example 1 of the present invention, the test results show that the traditional polyethylene oxide electrolyte has a thickness of about 90μm due to the lack of suitable matrix materials, but its mechanical properties are very poor, and a short circuit occurs after about 70 hours of circulation. When bacterial silk cellulose is added as the matrix of the electrolyte, the cycle life of the electrolyte is greatly enhanced due to the improvement of mechanical properties, and the lithium symmetric cycle can reach 450h, and the lithium deposition voltage of the two is basically equal, which is 16mV.

Claims

1. An ultra-thin polymer solid electrolyte membrane, characterized in that: The raw materials of the electrolyte membrane include nano-cellulose, high molecular polymer, solvent and electrolyte salt; in terms of mass ratio, nano-cellulose: high molecular polymer: solvent: electrolyte salt = (1-3): 20: (20-30): (6-16).

2. The ultra-thin polymer solid electrolyte membrane according to claim 1, characterized in that: The nano-scale cellulose is one of nano-cellulose and bacterial cellulose.

3. The ultra-thin polymer solid electrolyte membrane according to claim 1, characterized in that: The nano-scale cellulose has a cellulose purity of 90%-95%, a high Young's modulus of 15-35 GPa, and a tensile strength of 200-300 MPa.

4. The ultra-thin polymer solid electrolyte membrane according to claim 1, characterized in that: The solvent is one of water, acetonitrile, N-methylpyrrolidone and N,N-dimethylformamide.

5. The ultra-thin polymer solid electrolyte membrane according to claim 1, characterized in that: The high molecular polymer is one of polyethylene oxide, polyvinylidene fluoride and polyacrylonitrile.

6. The ultra-thin polymer solid electrolyte membrane according to claim 1, characterized in that: The electrolyte salt is one of LiTFSI, LiClO4, LiFSI, NaTFSI, and NaClO4.

7. A method for preparing an ultrathin polymer solid electrolyte membrane, characterized in that: The following steps are involved: Step 1, weigh nano-cellulose, high molecular polymer, solvent and electrolyte salt according to the mass ratio = (1-3): 20: (20-30): (6-16): Dispersing nano-cellulose in a solvent to obtain a nano-cellulose dispersion; in terms of mass ratio, nano-cellulose: solvent = (1-3): (20-30); Step 2, adding a high molecular weight polymer and an electrolyte salt to the nanometer-sized cellulose dispersion prepared in step 1 and mixing them evenly to obtain a polymer solid electrolyte precursor solution, wherein, by mass ratio, nanometer-sized cellulose: high molecular weight polymer: electrolyte salt = (1-3): 20: (6-16); Step 3, coating the polymer solid electrolyte precursor solution prepared in step 2 on a strippable carrier, using a scraper for scraping, with the scraper height set to (100-750 μm); Step 4, drying the electrolyte membrane obtained in step 3 until there is no water film on the surface, the drying temperature is 60-100°C, the drying time is 10min-20min, and the electrolyte membrane is obtained. Step 5, peel off the electrolyte membrane obtained in step 4 and vacuum dry it, the vacuum degree is 0-0.098MPa, the drying temperature is set to 80-100°C, and the drying time is set to 24-48h to obtain an ultra-thin polymer solid electrolyte membrane.

8. A solid-state polyethylene oxide battery, characterized in that: It includes the above-mentioned ultra-thin polymer solid electrolyte membrane.

9. The ultra-thin polymer solid electrolyte membrane according to claim 1, characterized in that: The raw materials of the electrolyte membrane include bacterial cellulose, polyethylene oxide, water and LiTFSI; in terms of mass ratio, bacterial cellulose: polyethylene oxide: water: LiTFSI=1:20:20:

6.

10. The method for preparing an ultrathin polymer solid electrolyte membrane according to claim 6 or 9, comprising the following steps: Step 1, dispersing bacterial cellulose in water to obtain a bacterial cellulose dispersion; the mass ratio of bacterial cellulose to water is 1:20; the bacterial cellulose has a cellulose purity of 90%, a high Young's modulus of 25 GPa, and a tensile strength of 200 MPa; Step 2, adding polyethylene oxide and LiTFSI to the bacterial cellulose dispersion prepared in step 1 and mixing them evenly to obtain a polymer solid electrolyte precursor solution, wherein the mass ratio of bacterial cellulose: polyethylene oxide: LiTFSI is 1:20:6; Step 3, coating the polymer solid electrolyte precursor solution prepared in step 2 on a strippable carrier, using a scraper for scraping, with the scraper height set to 100 μm; Step 4, placing the electrolyte membrane obtained in step 3 in a forced air oven, setting the oven temperature to 60° C. and drying for 10 min; Step 5, peel off the electrolyte membrane obtained in step 4, put it into a vacuum oven, set the vacuum degree to 0.02MPa, set the drying temperature to 80°C, and set the drying time to 24h to obtain an ultra-thin polymer solid electrolyte membrane.

Citation Information

Patent Citations

  • Preparation method and application of nano bacterial cellulose / polyoxyethylene composite solid electrolyte

    CN111969246A

  • Solid-state lithium battery and production method thereof

    CN113471542A

  • Preparation and application of ultrathin organic-inorganic composite solid electrolyte membrane

    CN114843590A

  • Topological structure all-solid-state polymer electrolyte and preparation method and application thereof

    CN115882060A